Kontribusi Pemikiran Muhammad Baqir Al-Sadr, Umar Vadillo, dan M. Umer Chapra dalam Membangun Paradigma Ekonomi Islam Kontemporer - Melisa Melisa; Nazla Sabirah; Raulanda Dwi Putra; Rissa Yulinda; Fitri Hayati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study examines the contribution of the thoughts of three important figures in modern Islamic economics, namely Muhammad Baqir al-Sadr, Ibrahim Umar Vadillo, and M. Umer Chapra. Using a qualitative approach through literature study, this research critically analyzes their works and ideas. The results of the study show that the three of them built three main pillars of the contemporary Islamic economic paradigm. The first pillar is normative-ethical which is asserted by al-Sadr, emphasizing the value of justice and ethics. The second pillar is the structural-monetary of Vadillo, who proposes a gold dinar and silver dirham-based monetary system for economic stability. The third pillar is Chapra's maqashid-policy, which emphasizes the application of sharia's maqashid principles to realize social welfare and economic justice. These three pillars complement each other in forming the foundation of an integral, applicable and relevant Islamic economy to face global challenges. This research makes an important contribution in formulating an adaptive and sharia-based Islamic economic framework.